Peningkatan Inklusi Keuangan Syariah melalui Penyaluran Dana Kepaada UMKM: Studi Kasus Pada BWM Tebuireng Jombang - Rosidayanti; Imam Sopingi; Peni Haryanti (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2023)
The importance of Islamic financial inclusion in supporting inclusive economic growth has become a major concern in recent years. One sector that plays an important role in economic growth is Micro, Small and Medium Enterprises (MSMEs). MSMEs are the backbone of the economy in many countries, including Indonesia. In addition, MSMEs can be a locomotive for the development of Islamic financial inclusion. The purpose of this study is to determine the increase in sharia financial inclusion through the distribution of funds to MSMEs. This research uses qualitative methods with a case study approach according to Robert K. Yin. The data collection techniques used, namely (1) Interviews with managers, supervisors and customers of BWM Tebuireng, (2) Documentation of BWM Tebuireng, (3) Archive records of BWM Tebuireng customer data, (4) Direct observation on MSMEs, (5) Physical devices at BWM Tebuireng, such as handphones and computers, were then analyzed using Ozil's theory related to financial inclusion and compared with several previous studies. The results of this study, namely increasing Islamic financial inclusion carried out by BWM Tebuireng through the distribution of funds to MSMEs have had a good impact on the surrounding community and especially MSME players as well as increasing Islamic financial inclusion.